Terrestrial gastropod diversity, distribution and abundance in areas with and without anthropogenic disturbances, Northeast Algeria - HADJER BELHIOUANI; MOHAMED EL-HADEF EL-OKKI; FATIMA-ZOHRA AFRI-MEHENNAOUI; LEILA SAHLI (Biodiversitas Journal of Biological Diversity, 2019)
Belhiouani H, El-Hadef El-Okki M, Afri-Mehennaoui FZ, Sahli L. 2019. Terrestrial gastropod diversity, distribution and abundance in areas with and without anthropogenic disturbances. Biodiversitas 20: 243-249. The objective of this study was to establish an inventory of terrestrial gastropods from different sites in the northeast of Algeria. Several points were sampled from five various areas relatively affected by human activity. Areas prospected were an industrial area (El-Hadjar, Annaba), a mining area (Djebel Hamimat, Oum-El-Bouaghi), an urban area (B’kira, Constantine), a mountainous area (Ibn Ziad, Constantine) and a sub-mountainous area (Ibn Badis, Constantine). A total of 11 species and 2632 individual land snails belonging to six molluscan families (Helicidae, Hygromiidae, Sphincterochilidae, Achatinidae, Enidae, and Pomatiidae) and 10 genera were found in all habitats. The highest density was recorded in the mountainous area with 1270 individuals and 10 species, whereas the lowest value was recorded in the mining and the industrial areas with 3 and 4 species respectively. The malacofaunal diversity was also determined, Shannon’s index, Simpson’s index, and equitability index are higher in the mountainous zone of Ibn Ziad with 1.87, 0.82 and 0.78 respectively, and lower in the mining area of Djebel Hamimat, with 0.60, 0.33, and 0.54. The dispersion and density of species appear to be contingent upon several factors among which soil properties, height, climate conditions and certainly anthropogenic disturbance.